Respuesta :

Answer:

x = 1

Step-by-step explanation:

[tex] {7}^{(4x - 6)} = \frac{1}{49} \\ \\ \implies {7}^{(4x - 6)} = \frac{1}{ {7}^{2} } \\ \\ \implies {7}^{(4x - 6)} = {7}^{ - 2} \\ \\ \implies \: 4x - 6 = - 2 \\ \\ \implies \: 4x = 6 - 2 \\ \\ \implies \: 4x = 4 \\ \\ \implies \: x = \frac{4}{4} \\ \\ \implies \: x = 1[/tex]

Answer:

x = 1

Step-by-step explanation:

Using Definition of Logarithm

7 ^(4x−6) = 1/49

​Use the rules of exponents and logarithms to solve the equation.

7 ^(4x−6) = 1/49

​Take the logarithm of both sides of the equation.

log(7^4x-6) = log(1/49)

The logarithm of a number raised to a power is the power times the logarithm of the number.

(4x-6)log(7) = log(1/49)

Divide both sides by log(7).

4x-6 = log(1/49)/log(7)

​By the change-of-base formula log(a)/log(b) = log(small b under) (a).

4x-6 = log(small 7 under) (1/49)

Add 6 to both sides of the equation.

4x=−2−(−6)

Divide both sides by 4.

x = 4/4 which is the same as x = 1